Altered cerebral perfusion measured by SPECT in relatives of patients with schizophrenia. Correlations with memory and P300. - Blackwood, D; Glabus, M; Dunan, J; O'Carroll, R; Muir, W; Ebmeier, K (1999)
BACKGROUND: Genetic studies in schizophrenia are hampered by the complex heterogeneous clinical phenotype. Biological variables identified as trait markers of risk could clarify the mode of inheritance, define clinical subgroups and provide clues about aetiology. AIMS: To use single photon emission computed tomography (SPECT) to compare brain perfusion maps in patients with schizophrenia (n = 19), their asymptomatic 'high-risk' relatives (n = 36) and control subjects (n = 34) and to examine the relationships between imaging, memory and P300 event-related potential. METHOD: SPECT, memory tests and P300 recording were carried out. RESULTS: In the patients with schizophrenia and their relatives, perfusion was reduced in left inferior prefrontal and anterior cingulate cortex and increased bilaterally in a subcortical region. Perfusion significantly correlated with verbal memory and P300 amplitude in left inferior prefrontal cortex and with P300 latency in anterior cingulate cortex. CONCLUSIONS: Medication- and symptom-free relatives had altered regional perfusion intermediate between subjects with schizophrenia and controls. Impaired perfusion, verbal memory and P300 appear to be related traits associated with an increased risk of illness.